Insulin and non-esterified fatty acid relations to alimentary lipaemia and plasma concentrations of postprandial triglyceride-rich lipoproteins in healthy middle-aged men. - Boquist, S; Hamsten, A; Karpe, F; Ruotolo, G (2000)
AIMS/HYPOTHESIS: Enhanced and prolonged postprandial lipaemia is related to cardiovascular disease but how postprandial lipaemia is regulated is poorly known. We therefore determined the relations of fasting insulin concentrations to fasting and postprandial lipids, lipoproteins and non-esterified fatty acids in middle-aged men. METHODS: The subjects, 99 healthy 50-year-old men with an apolipoprotein E3/3 genotype, ate a mixed meal. The apolipoprotein B-48 and B-100 contents were determined in triglyceride-rich lipoproteins as a measure of chylomicron remnant and very low density lipoprotein particle concentrations. RESULTS: Fasting plasma insulin was associated with the triglyceride response to the test meal, independently of body mass index, waist-to-hip circumference ratio, blood glucose and the insulin effect on fasting plasma triglycerides. Exaggerated and prolonged postprandial lipaemia in subjects in the upper quartile of the plasma insulin distribution was largely accounted for by large (Svedberg flotation rate > 60) very low density lipoproteins and chylomicron remnants. Insulin relations to large postprandial triglyceride-rich lipoproteins exclusively reflected the association between plasma insulin and the fasting plasma concentrations of these lipoprotein species, whereas plasma insulin and late postprandial plasma concentrations of small (Svedberg flotation rate 20-60) chylomicron remnants were related, independently of insulin influences on fasting concentrations. Strong positive relations were found between the late increases in large triglyceride-rich lipoproteins and plasma non-esterified fatty acid concentrations after 6 h. CONCLUSION/INTERPRETATION: The degree of insulin sensitivity is a major determinant of postprandial lipaemia in healthy middle-aged men and could add to the regulation of the basal production of large triglyceride-rich lipoproteins.